The Thermal Activation of Serpentinite from the Zhitikarinsky Deposit (Kazakhstan) - Abdrazak Auyeshov; Kazhymuhan Arynov; Asem Satimbekova; Chaizada Yeskibayeva; Kurman Alzhanov (Molecules)
Changes in the phase composition of serpentinite from the Zhitikarinsky deposit (Kazakhstan) were studied during heat treatment in the temperature range of 105–800 °C in order to determine the phase that leads to an increase in the reactivity of serpentinite during interactions with acids. In accordance with this, the task was set to consider the influence of temperatures (105 °C, 600 °C, 660 °C, 725 °C, 750 °C and 800 °C), selected according to the extreme points of the main transformations from its derivatogram, on changes in the phase composition. The effects of heat treatment on the phase composition and reactivity of serpentinite during interactions with sulfuric acid were studied and discussed using the diffraction patterns of serpentinite heat treated at selected temperatures for 1 h and using methods of thermodynamic evaluation of the possible reactions in the temperature range of 350–750 °C, as well as establishing the nature of their interaction with sulfuric acid under identical conditions. It has been shown that, in the range of 600–750 °C, the crystal lattice of the structural composition of serpentinite is completely destroyed with the formation of not only magnesium silicates but possibly also magnesium oxide, which leads to the thermal activation of serpentinite in relation to interactions with acids and the improvement of the technological process of extracting magnesium from it. The greatest increase in reactivity was found in serpentinite samples heat treated at temperatures of 725 °C and 750 °C, which can be recommended for the thermal activation of serpentinite before using acid methods to improve the technological performance of the process of extracting magnesium from serpentinite.